Synthesis-enabled exploration of chiral and polar multivalent quaternary sulfides. Issue 44 (19th October 2021) - Akopov, Georgiy; Hewage, Nethmi W.; Yox, Philip; Viswanathan, Gayatri; Lee, Shannon J.; Hulsebosch, Liam P.; Cady, Sarah D.; Paterson, Alexander L.; Perras, Frédéric A.; Xu, Wenqian; Wu, Kui; Mudryk, Yaroslav; et al.
Abstract : Synthesis from atomically-mixed precursors opens up a phase space to hundreds of chiral and polar sulfide semiconductors with almost any transition metal in variable oxidation states. Abstract : An innovative method of synthesis is reported for the large and diverse (RE)6 (TM) x (Tt)2 S14 (RE = rare-earth, TM = transition metals, Tt = Si, Ge, and Sn) family of compounds (∼1000 members, ∼325 contain Si), crystallizing in the noncentrosymmetric, chiral, and polar P 63 space group. Traditional synthesis of such phases involves the annealing of elements or binary sulfides at elevated temperatures. The atomic mixing of refractory components technique, presented here, allows the synthesis of known members and vastly expands the family to nearly the entire transition metal block, including 3d, 4d, and 5d TMs with oxidation states ranging from 1+ to 4+. Arc-melting of the RE, TM, and tetrel elements of choice forms an atomically-mixed precursor, which readily reacts with sulfur providing bulk powders and large single crystals of the target quaternary sulfides. Detailed in situ and ex situ experiments show the mechanism of formation, which involves multiphase binary sulfide intermediates. Crystal structures and metal oxidation states were corroborated by a combination of single crystal X-ray diffraction, elemental analysis, EPR, NMR, and SQUID magnetometry. The potential of La6 (TM) x (Tt)2 S14 compounds for non-linear optical applications was also demonstrated.